Gambaran Pengetahuan Masyarakat Tentang Pencegahan Penyakit Multidrug Resistant Tuberculosis Di Puskesmas Ujungberung Indah Kota Bandung - Pratidina, Eki; Fatmaningsih, Vivi Yulia (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2019)
Multi Drug-Resistant Tuberculosis (MDR-TB) is a TB case that causes the bacilli Mycobacterium tuberculosis that is resistant to rifampicin and isoniazid. Based on reports from the TB Control Program in West Java, in 2016 there were 68,000 TB cases and caseswere published. While from the entire population of West Java, it is estimated that TB in 2016 will be 316 / 100,000 or approximately 149,600 cases. Thus, there are still 81,000 (54%) TB cases that are not reported, so this can be a source of TB transmission in the community. The purpose of this research was to find out the description of the community about Multi-Resistant Tuberculosis (MDR-TB) at UPT Ujung Berung Indah Health Center, Bandung. The research method uses the descriptive method, with the participation of Tuberculosis sufferers in the last 2 months received at UPT Ujungberung Indah Health Center as many as 75 people. Time Required for 1 week, with accidental sampling technique. The research instrument used a questionnaire sheet. The results showed the fact of community knowledge about MDR-TB a small proportion of respondents (44.0%) as many as 33 respondents had sufficient knowledge, a small portion of respondents (39%) as many as 29 respondents had good knowledge, and very few respondents (17, 0 %) as many as 13 respondents have less knowledge. The conclusion of the research from the description of the community about MDR-TB disease in UPT Ujungberung Indah Health Center, Bandung City, has a sufficient level of knowledge.